Eficiencia del manejo agroecológico de la principal plaga Spodoptera frugiperda del cultivo de maíz (Zea mays L.) en la época lluviosa. - Pilla Bardales, Luis Carlos (2021)
The presence of pests still persists in the corn crops being the factors that limit their production and productivity, among which we find; the bud of the corn, which can affect the crop in its physiology as cutter, borer, bud and damaging the cobs. For this reason, alternative methods to control fall armyworm were sought, in order not to use chemicals. This study was carried out in two localities of the Mocache Canton, Province of the Rivers, with the aim of developing a technology for the agroecological management of the bud worm (Spodoptera frugiperda) in corn, presenting as treatments in study Beauveria Bassiana (4; 6 and 5 litres/ha) + Neem extract (1.8 litres/ha). The experiment was developed in two locations such as Pechiche and Las Palmas. The experimental design used was complete randomized blocks (BCA) with 4 treatments and 4 repetitions; for the comparison of means, the Tukey test was used at 5% probability. According to the results obtained, different insects beneficial for the agroecological control of Spodoptera frugiperda were found in the study area, among which are Crisopa sp, Cycloneda sanguinea and Coleomegilla maculata observing 423, 367 and 207 specimens, respectively. Beauveria bassiana (4 litres/ha) + Neem extract (1.8 litres/ha) proved to be the most effective and effective in the variables number of healthy cobs, number of diseased cobs, number of rows per cob, weight of 100 seeds and number of grains per row both in the town of Pechiche and in Las Palmas. The bioinsecticide demonstrated its controlling effect in populations of Spodoptera frugiperda and improved agronomic behavior of the crop in both locations under study. Key words: Agroecological management, bioinsecticide, Beauveria bassiana, Neem.